2013
DOI: 10.19041/apstract/2013/1/4
|View full text |Cite
|
Sign up to set email alerts
|

Success factors of international sporting events in different regions of Europe

Abstract: Sport events always played an important role in human life from the ancient Olympics and marathon races to today’s modern Olympics, World and continental championships. In our days these remarkable sport events come to the fore because participants of the sporting world effectuate even more, greater and more varied ones. Furthermore, the competition for organisation between cities and countries is becoming more and more intense (Zeman 2005). The organisation of international sporting events is an extremely com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 9 publications
1
3
0
Order By: Relevance
“…The study significantly found that effective communication is essential for successful event during the climate variability and change. This is in line with previous study by Cserháti and Polák-Weldon (2010) which indicated that cooperation and communication among the stakeholders are two important aspects in determining the successful of sporting event.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The study significantly found that effective communication is essential for successful event during the climate variability and change. This is in line with previous study by Cserháti and Polák-Weldon (2010) which indicated that cooperation and communication among the stakeholders are two important aspects in determining the successful of sporting event.…”
Section: Discussionsupporting
confidence: 92%
“…There were a total of 57 final year students taking Event Management Program by December 2017. The questionnaire for this study was adopted and adapted from previous literature relating to the topic for instance Cserháti and Polák-Weldon (2010), Burger and Saayman (2009) and Glover (2010). Data gained from the survey were analysed for descriptive statistics using a Statistical Package for Social Sciences, version 19.0 created by SPSS.…”
Section: Methodsmentioning
confidence: 99%
“…However, these firms must implement a variety of evolving sponsorship program protection strategies because the publicity and consumer audiences generated by sports events provide attractive marketing opportunities for companies other than the events’ official sponsors (Mckelvey and Grady, 2008). Finally, sports promoters must manage participants’ duties and activities and co-ordinate these contributors’ work to ensure events satisfy the needs of international sports associations, sponsors and other stakeholders (Cserháti and Polák-Weldon, 2013).…”
Section: Literature Reviewmentioning
confidence: 99%
“…DMOs also strategically use sport events to create a distinct brand image for the destination (Chalip and Costa, 2006). In their study of eight European countries between 2000 and 2008, Cserhati and Polak-Weldon (2013) suggest key success factors of the organising committees of international sporting events include objective and task planning, contract strategy, leadership, organisational culture, cooperation and communication and partnership. Also, Kaplanidou et al (2013) found that effective event management and delivery were two common factors to both event providers and spectators.…”
Section: Literature Reviewmentioning
confidence: 99%